Structure preserved : studies in syntax for Jan Koster - Zwart, C. Jan-Wouter; Vries, Mark de, 1973-; Koster, Jan, 1945- (Linguistik aktuell, 2010)
"Structure is at the rock-bottom of all explanatory sciences" (Jan Koster). Forty years ago, the hypothesis that underlying the bewildering variety of syntactic phenomena are general and unified structural patterns of unexpected beauty and simplicity gave rise to major advancements in the study of Dutch and Germanic syntax, with important implications for the theory of grammar as a whole. Jan Koster was one of the central figures in this development, and he has continued to explore the structure preserving hypothesis throughout his illustrious career. This collection of articles by over forty.